2021
DOI: 10.22495/jgrv10i3art5
|View full text |Cite
|
Sign up to set email alerts
|

Labour regulation in the public sector: Employment relationship, employment relations satisfaction and psychological contract

Abstract: This paper aims to report on the outcome of the study that investigated the cause of the ongoing antagonistic employment relationship (ER) in the South African public sector workplace, which has negatively affected employment relations satisfaction (ERS) and psychological contract (PC) fulfilment. This antagonism between management and employees has lowered the levels of employer-employee trust (Sudiarta, 2021), as well as job satisfaction (Silitonga et al., 2020) in the workplace. This study, therefore, explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Studies on workplace relationships reveal that negative workplace relationships affect the team interaction and performance, as well as the commitment of the employees towards the organisation (Duan et al 2018 ; Harms et al 2018 ; Shen et al 2019 ). Conflicts between the nurse managers and unions are expected and should be resolved amicably to prevent negative workplace relationships that may result to poor employee performance (Ntimba 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies on workplace relationships reveal that negative workplace relationships affect the team interaction and performance, as well as the commitment of the employees towards the organisation (Duan et al 2018 ; Harms et al 2018 ; Shen et al 2019 ). Conflicts between the nurse managers and unions are expected and should be resolved amicably to prevent negative workplace relationships that may result to poor employee performance (Ntimba 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smith and Diedericks ( 2016 ) concluded that communication issues and a lack of teamwork between the union leaders and managers deny these two parties an opportunity to learn and grow from each other. Ntimba ( 2019 ) stated that unfortunately, the workplace is still characterised by antagonistic relations between managers and unions leaders who represent the employees in unionised work organisations. Nurse managers and union leaders should be working as a team and not against each other as this changes the negative perceptions that the nurse managers have on workplace relationships.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations